La calidad de servicio y su relación con las ventas en los hoteles tres estrellas de Iquitos – 2023 - Eguren Flores, Samuel Augusto (2024)
The objective of this research was to determine the relationship of service quality with sales in three-star hotels in the city of Iquitos, 2023, the methodology was correlational, descriptive, non-experimental design, the sample consisted of 23 managers of three-star hotels. The results obtained are: the dimensions of service quality: tangible elements, empathy, reliability, responsiveness and security in three-star hotels are related to sales management with (p= 0.012, p=0.026, p=0.026, P=0.005, and p=0.043 respectively). Only responsiveness is related to sales type (p=0.034). Sales technique has no significance in this study. The research concludes that the quality of service in three-star hotels in Iquitos is related to the sales variable at 5% significance (p=0.025).